Chemical looping electricity storage. (1st December 2020) - Saghafifar, Mohammad; Schnellmann, Matthias A.; Scott, Stuart A.
Highlights: A new grid-scale electricity storage system is introduced using chemical looping. Energy and exergy analyses are carried out on the chemical looping electricity storage. Material screening is carried out to identify the most ideal material properties. Comparative analysis is carried out between this technology and other grid-scale electricity storage systems. Abstract: Developing grid-scale energy storage technologies is the key element for broader deployment of renewable sources of energy. This paper examines a simple cycle which makes use of a thermo-chemical store, with a view to achieving high storage capacity by using the chemical looping concept. Results show that a Chemical Looping Electricity Storage (CLES) system can achieve a very high capacity, in the range of 250–350 kWh/m 3, second only to hydrogen electricity storage systems. Its round-trip efficiency (40–55%) is potentially higher than that of the hydrogen electricity storage systems. By achieving a higher capacity than pumped thermal energy storage and higher round-trip efficiency than that of hydrogen systems, CLES has the potential to fill out the gap between these two grid-scale storage technologies. Thus, this system may play an important role in our future energy mix because, unlike hydrogen storage, it can achieve a high storage capacity without a huge penalty on its round-trip efficiency.